2008
DOI: 10.1007/s00134-008-1148-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and mortality due to sepsis, severe sepsis and septic shock in Italian Pediatric Intensive Care Units: a prospective national survey

Abstract: The descriptor is pediatrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 25 publications
3
66
2
5
Order By: Relevance
“…The hospital mortality rate of 25% confirms that severe sepsis remains a critical public 23 (12-28) 20 (5-26) 21 25 (19-28) 26 (20-28) 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 22 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) ,0.001…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The hospital mortality rate of 25% confirms that severe sepsis remains a critical public 23 (12-28) 20 (5-26) 21 25 (19-28) 26 (20-28) 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 22 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) ,0.001…”
Section: Discussionmentioning
confidence: 88%
“…Vasoactive medications were used in 55%, with significant variation across age groups (P = 0.01) and the highest use in infants aged 29 days to 1 year (see Table E3). Vasoactive medications were used for a median of 7 (IQR,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) days. Epinephrine and norepinephrine were the most commonly used medications, at 43% and 42% of patients treated with vasoactive medications, respectively, and dopamine was used in 32%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high mortality of septic shock in children was confirmed in a paper from Wolfler et al [6] who reported a prospective observational study across 15 Italian paediatric intensive care units conducted over a period of 1 year. During the study 2,741 children were admitted to the participating PICU's.…”
Section: Paediatricsmentioning
confidence: 80%